Adventure tourism: participation motivation and revisit intention in Gopeng, Perak / Zulkifli Mamat, Nor Hidayu Shamsuddin and Nurul Adibah Mohd Ariff - Mamat, Zulkifli; Shamsuddin, Nor Hidayu; Mohd Ariff, Nurul Adibah (2014)
This research explores the relationship between the participant motivation and the reintention behavior among the participants towards adventure tourism in Gopeng, Perak. Specifically, the aim of this study is threefold: (a) To identify the attributes or elements of adventure tourism in Gopeng, Perak; (b) To investigate the best dimension of adventure tourism towards motivation and (c) To investigate the relationship between motivation and revisit. The adventure tourism is a subset of tourism that is rapidly growing in popularity. Data were collected from 150 visitors who were enjoyed and experienced the adventure activities at Gopeng, Perak areas. The survey instrument assessed the motivation that motivates the participants to enjoy the activities and what most motivate them to re-intention behavior to come again. The results of a motivation factor, which is pull and push factor revealed what motivation most influence participant to enjoy the activity. As the result, the activity that most influence the participants to do a re-intention behavior in Gopeng, Perak is water abseiling and most motivate them is to experiencing new and different lifestyles.